Effect of Compound Additives on Nutritional Composition, Fermentation Quality, and Bacterial Community of High-Moisture Alfalfa Silage - Heng Jiang; Haoran Wang; Buhe Bao; Hui Qu; Jiao Wang; Le Sun; Bin Liu; Fengqin Gao (Fermentation, 2023)
The wilting process is required for the preparation of traditional low-moisture silage, which is not only subject to the interference of rainfall during the harvest season in many areas, but also increases labor, economic, and time costs. Therefore, in this experiment, newly harvested alfalfa was supplemented with a complex additive consisting of lactic acid bacteria (LAB), sucrose, and corn flour, and then ensiled directly in order to explore a suitable high-moisture silage processing method. There were four groups: control (CK), 0.01 g/kg LAB plus 2% sugar (S), 0.01 g/kg LAB plus 5% corn flour (C5), and 0.01 g/kg LAB plus 5% corn flour (C10). The results show that all four types of silage had significantly reduced acid detergent fiber, acetic acid content, and ammonia/total nitrogen (p < 0.05). The relative abundance of Lactobacillus spp. was significantly higher (p < 0.05), and that of Weissella, Clostridium sensu stricto 12, and Pantoea genera was significantly lower (p < 0.05) in all four treatments. Group S had significantly increased crude protein content, and groups C5 and C10 had significantly reduced neutral detergent fiber. Overall, group C10 had the highest LA concentration, the highest relative abundance of Lactobacillus spp., and the lowest pH, ammonia/total nitrogen, neutral detergent fiber, and acid detergent fiber. Silage with a complex additive consisting of LAB + 10% corn flour is recommended to achieve good fermentation with high nutritional quality.